Relationship between organizational environmental management practices and employees’ organizational citizenship behaviour toward the environment - eco initiatives: The influence of affective commitment towards the environment - Soon-Yew, Ju; Diyana, Kamarudin; Thurasamy, Ramayah; Noor Azlinna, Azizan (Widad, 2018)
An emergent body of knowledge has acknowledged that there is a relationship between organizational environmental management practices and the employees’ organizational citizenship behaviour toward the environment. Nonetheless, there is very little that is known about mediating mechanisms that trigger the establishment of this relationship. Based on the social exchange theory, the study explores the possibility of affective commitment towards the environment as an indirect effect of the relationship between environmental management practices and the employees’ organizational citizenship behaviour toward the environment - eco initiatives. This research model is analysed using the information gathered from 244 employees working with local authorities in Peninsular Malaysia. Respondents answered questionnaires to measure their perceptions toward environmental management practices, affective commitment towards environment, and organizational citizenship behaviour toward the environment - eco initiatives. The analysis made on the indirect effect has revealed that the affective commitment towards the environment has mediated the relationship that exists between environmental management practices and the employees’ organizational citizenship behaviour toward the environment - eco initiatives.